2015
DOI: 10.1186/s12889-015-1774-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of use of non-prescription analgesics in the Norwegian HUNT3 population: Impact of gender, age, exercise and prescription of opioids

Abstract: BackgroundThere are concerns about potential increasing use of over-the-counter (OTC) analgesics. The aims of this study were to examine 1) the prevalence of self-reported use of OTC analgesics; 2) the prevalence of combining prescription analgesics drugs with OTC analgesics and 3) whether lifestyle factors such as physical activity were associated with prevalence of daily OTC analgesic use.MethodsQuestionnaire data from the Nord–Trøndelag health study (HUNT3, 2006–08), which includes data from 40,000 adult re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
50
2
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 15 publications
15
50
2
10
Order By: Relevance
“…[10,20,21] Our findings generally revealed no significant difference in use of analgesics between male and female as the previous study in Iran and that converse to other studies in Riyadh, Taif, turkey, Germany, and Norway. [1,14,15,17,22,23] Like our findings in Saudi, many studies have also shown there is a significant age difference in the prevalence of analgesic use among the population. Studies conducted in Taif, Sweden, United States, and Norway have shown an association between age and analgesic use.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…[10,20,21] Our findings generally revealed no significant difference in use of analgesics between male and female as the previous study in Iran and that converse to other studies in Riyadh, Taif, turkey, Germany, and Norway. [1,14,15,17,22,23] Like our findings in Saudi, many studies have also shown there is a significant age difference in the prevalence of analgesic use among the population. Studies conducted in Taif, Sweden, United States, and Norway have shown an association between age and analgesic use.…”
Section: Discussionsupporting
confidence: 43%
“…This agrees with results from previous studies. [14,16] there is another study in Germany shown the opposite result. [17] Most of the analgesics user in this study are taking one tablet mostly for minor pains such as fever and headache which shows lack of information about appropriate adult dose which agrees with a Norwegian study which says that their respondents were using a lower dose of OTC drugs and had not exceeded the maximum dose.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, some of these variables have been identified in recent literature, as factors associated with OTC use. For example, adults with little physical activity had 1.5-4 times greater risk of daily OTC analgesic use compared to physically active individuals (34).…”
Section: Discussionmentioning
confidence: 99%